Metode Diskusi Panel Untuk Meningkatkan Keterampilan Berkomunikasi Di Madrasah Ibtidaiyah - Hayati, Nofrita Mauliza; Setiyawati, Dewi (GHAITSA : Islamic Education Journal, 2020)
This research was conducted with the aim of improving communication skills in Indonesian language learning in class VI MI Az Zahra Cangkreplor, Purworejo Regency by using the panel discussion method. This research is a classroom action research conducted in two cycles, namely cycle I, cycle II. The results of the research that had been carried out in cycle I, the minimum completeness percentage was still below the minimum completeness limit, namely, only 30.00. In cycle II, the minimum completeness percentage is 80.00. These results indicate that the results in cycle II have increased by 50.00 from the results in cycle I, and the percentage of minimum completeness in cycle II has exceeded the minimum completeness criteria (KKM). The KKM in Indonesian for grade VI MI Az Zahra Cangkreplor, Purworejo Regency is 70.00. Thus the panel discussion method can improve communication skills in Indonesian Language Learning in class VI MI Az Zahra Cangkreplor, Purworejo Regency.